Postal Voting In the 2020 Presidential Election – How Did Electoral Participation Evolved During the COVID-19 Pandemic? - Musiał-Karg, Magdalena (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2022)
Issues related to electoral participation are extremely complex, not least because of the different approaches of researchers to the issue. The COVID-19 pandemic has contributed to specialists, lawyers, political scientists addressing the issue of electoral participation in the context of public health risks and the implementation of the principle of universality of elections. In order to provide greater guarantee of the principle of universality, many countries are introducing additional forms of voting in elections other than voting at the polling station. Postal voting is one of the alternative voting methods that appears to be the most popular in terms of participation in elections. It exists in different forms in different countries. In Poland, in 2020, there were attempts to implement all-postal voting at first, and then – after the second elections were held – it was decided to use hybrid voting. The aim of this article is to analyze the Polish experience with postal voting in 2020 in the context of the implementation of this tool during the pandemic.

Zagadnienia związane z partycypacją wyborczą są wyjątkowo złożone, m.in. ze względu na różne podejścia badaczy do tej problematyki. Pandemia COVID-19 przyczyniła się do podejmowania przez specjalistów, prawników, politologów kwestii partycypacji wyborczej w kontekście zagrożenia zdrowia publicznego i realizacji zasady powszechności wyborów. Aby zapewnić większą gwarancję zasady powszechności, w wielu państwach wprowadza się dodatkowo inne niż głosowanie w lokalu wyborczym formy oddawania głosu w wyborach. Głosowanie korespondencyjne jest jedną z alternatywnych metod głosowania, która wydaje się najbardziej popularną w kontekście udziału w elekcjach. W rożnych państwach występuje ona w różnych formach. W Polsce w 2020 usiłowano wdrożyć najpierw all-postal voting, a następnie – po rozpisaniu drugich wyborów – zdecydowano się na głosowanie hybrydowe. Celem niniejszego artykuły jest analiza polskich doświadczeń z głosowaniem korespondencyjnym w 2020 r. w kontekście zastosowania tego narzędzia w czasie pandemii.
Głosowanie korespondencyjne w wyborach prezydenckich roku 2020 – jak kształtowano partycypację wyborczą w czasie pandemii COVID-19?
Keywords: participation; elections; postal voting; all-postal voting pandemic; COVID-19; elections; Poland; partycypacja; wybory; głosowanie korespondencyjne; wyłączne głosowanie korespondencyjne; pandemia; COVID-19; Polska